Combination of in-situ diffraction experiments and acoustic emission testing to understand the compression behavior of Mg-Y-Zn alloys containing LPSO phase under different loading conditions. (July 2018) - Garcés, G.; Máthis, K.; Medina, J.; Horváth, K.; Drozdenko, D.; Oñorbe, E.; Dobroň, P.; Pérez, P.; Klaus, M.; Adeva, P.
Abstract: The effect of the orientation of the non-recrystallized grains (non-DRX) and the LPSO phase on plasticity in extruded MgY2 Zn1 alloy with a bimodal grain structure have been studied in-situ using the combination of synchrotron diffraction and acoustic emission techniques during compression tests. The adaptive sequential k-means (ASK) procedure was applied to analyze the acoustic emission signal. This method can successful separate the signal for each possible deformation systems. Combining both techniques, the deformation mechanisms that take place during the compression tests under different loading directions have been distinguish. Independently of the loading direction, the beginning of the macroscopic plasticity is always controlled by the activation of basal slip system in the DRX grains. However, highly oriented non-DRX grains and LPSO phase have a strong influence over the compressive deformation of the MgY2 Zn1 alloy. The basal planes in the non-DRX grains were oriented parallel to the extrusion direction (ED). Thus, the activation of the 10 1 ¯ 2 〈 10 1 ¯ 1 ¯ 〉 extension twinning was found to be significant only in the ED mode. In the other two loading cases, TD and 45, the activation of non-basal slip systems has been detected. On the other hand, the reinforcing effect of the elongated LPSO phase is the most effective, if the loading axis is aligned with the fiber direction (extrusion direction) since the load transfer mechanism is more effective. In this loading case, the LPSO can be plastically deformed due to kinking. This deformation mode has been isolated by the ASK procedure and characterized by in-situ scanning electron microscopy. Graphical abstract: Image 1 Highlights: Effect of the orientation of the non-DRX grains and the LPSO phase in the compression behaviour. Combination of in-situ synchrotron diffraction and acoustic emission experiments to study the anisotropic behavior. Plasticity of non-DRXed and DRXed grains and LPSO phase due to the activation of basal slip, tensile twinning and kinking. The reinforcing effect of the LPSO phase is investigated.